Preserving Saccharomyces cerevisiae Culture for Bee Health and Production - Aakriti Gusain; Akhil Kumar (International Journal of Insects, 2024)
Saccharomyces cerevisiae, a single-celled fungus also known as baker’s and brewer’s yeast, is extensively used in brewing, baking, and winemaking due to its robust genetics and utility as a model organism in scientific research. Its role extends beyond these applications into apiculture, where it is utilized to produce supplements and pollen replacements for honeybees. These yeast-based supplements are crucial, especially during times of pollen scarcity or colony stress, as they provide essential minerals, proteins, and amino acids necessary for maintaining healthy and productive bee colonies. By enhancing the diet of honeybees, these supplements not only support their general health but also improve their resistance to infections and diseases. Yeast-based diets contribute significantly to the overall vitality of bee colonies, ensuring they remain resilient and effective even under challenging conditions. The successful production and application of S. cerevisiae require careful attention to strain selection, culture maintenance, and optimal growth conditions. Effective scaling-up processes and meticulous storage and handling are essential to preserve the yeast’s genetic stability and viability. These practices ensure the yeast’s performance and quality in various industrial uses. By adhering to these guidelines, consistent and high-quality yeast cultures can be achieved, supporting both biotechnological applications and apicultural practices. Thus, S. cerevisiae plays a pivotal role in both scientific research and practical applications, including the enhancement of bee health and productivity.
Keywords: Bee colonies; Bee health; Culture; Honeybees; Saccharomyces cerevisiae